PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TAI DAN PROBLEM BASED LEARNING (PBL) TERHADAP PEMAHAMAN KONSEP BANGUN RUANG SISWA - Lia Budi Tristanti (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
The objective of the research is to describe whether there is a difference of students' understanding of mathematical concepts using cooperative learning model of TAI type and Problem Based Learning (PBL) and show the cause of the difference. This study included experimental research with randomized control group design pretest posttest design. The result of the research shows that (1) the understanding of students 'mathematical concepts with cooperative learning model of TAI type is not significantly different from the understanding of students' mathematics concept with PBL learning model; (2) the understanding of students 'mathematical concept with cooperative learning model of TAI type is not significantly different from the students' with conventional learning model, (3) understanding of student math concept with PBL learning model is significantly different with understanding of student math concept with conventional learning model. So that there is effect of cooperative learning model of TAI type and problem based learning (PBL) to the students' math concept.